Micro-marsupialization: A minimally invasive technique for mucocele in children and adolescents - S K Sagari; K C Vamsi; D Shah; V Singh; G B Patil; S Saawarn (Wolters Kluwer Medknow Publications, 2012)
Background: Most common lesions seen in children are mucoceles. Different techniques have been described for their treatment; however, most of them are invasive. Objective: Aim of the study was to compare the practicability of micro-marsupialization with surgical excision in treatment of mucoceles. Materials and Methods: A pilot study was done on 15 patients to evaluate and compare variables like lesion evolution, surgical time period, healing, complications etc. when lesions were treated with micro-marsupialization and surgical excision. Results: Most of the mucoceles diagnosed in this pilot study were found in lower lip. Amongst cases that were treated with micro-marsupialization, recurrence was seen only in one case, whereas there were 3 cases of recurrence seen in surgical excision group. No statistically significant difference was found between the treatment methods used. Conclusion: Micro-marsupialization can be a non-invasive option to treat mucoceles in pediatric dentistry owing to its simplicity, fewer complications involved and as well that it's well-tolerated by patients.